2016
DOI: 10.1186/s13287-016-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Local injection of bone marrow progenitor cells for the treatment of anal sphincter injury: in-vitro expanded versus minimally-manipulated cells

Abstract: BackgroundAnal incontinence is a disabling condition that adversely affects the quality of life of a large number of patients, mainly with anal sphincter lesions. In a previous experimental work, in-vitro expanded bone marrow (BM)-derived mesenchymal stem cells (MSC) were demonstrated to enhance sphincter healing after injury and primary repair in a rat preclinical model. In the present article we investigated whether unexpanded BM mononuclear cells (MNC) may also be effective.MethodsThirty-two rats, divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…This theory was confirmed by the findings of Mazzanti et al . who concluded that mononuclear cells of the bone marrow and mesenchymal stem cells are equally effective as an adjunct to primary repair for the management of anal sphincter injuries in the animal model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This theory was confirmed by the findings of Mazzanti et al . who concluded that mononuclear cells of the bone marrow and mesenchymal stem cells are equally effective as an adjunct to primary repair for the management of anal sphincter injuries in the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Mazzanti et al . have demonstrated in a preclinical model on rats that minimally manipulated bone marrow mononuclear cells are as effective as in vitro expanded mesenchymal stem cells for the recovery of anal sphincter injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most immunological disorders, intravenous administration has been the route of choice whereas for bone repair purposes, MSCs are seeded on transplantable scaffolds or administered as in vitro generated cartilaginous templates that undergo osteogenic differentiation after implantation . For treatment of other types of tissue injuries, MSCs have been applied into the wound area via local injections .…”
Section: Mechanism Of Action; Current State Of the Artmentioning
confidence: 99%
“…Recently Fitzwater et al noticed that the administration of rat myogenic stem cells enhanced the contractile function of the sphincter without significant changes in histologic morphology, which addresses the paracrine processes in stem cell therapy 14. To simplify the cell isolation and proliferation process, Mazzanti et al used freshly isolated minimally manipulated bone‐marrow derived mononuclear cells without expansion and found them to be as effective as in vitro expanded BM‐MSCs in the recovery of iatrogenic anal sphincter rupture 38. Muscle‐derived stem cell injections have been used in small pilot studies in women and the results are promising 39, 40, 41.…”
Section: Discussionmentioning
confidence: 99%